Kinetika Reaksi Poliesterifikasi Hidrolisat Shellac dan Anhidrida Ftalat Ditinjau Dari Reaktivitas Gugus Hidroksil - Saputri, Lestari Hetalesi; Rochmadi, Rochmadi; Budhijanto, Budhijanto (Universitas Ahmad Dahlan, 2015)
This research presents polyesterification kinetics for shellac hydrolizate-phtalic anhydride. The polyesterification kinetics is proposed by assuming that the reaction Â in ideal system, whereas the reactivity of the OH groups are considered different. Polyesterification was started from purification of shelllac by hydrolisis process. Hydrolisis was done by dissolving seedlac into NaOH solution and acidification with HCl. Polyesterification was conducted by reacting shellac hydrolizate with phtalic anhydride. Both of these materials were reacted in a three necked flask under vacuum condition. The reaction was conducted in temperature range of 130-170 0C and samples were taken every 30 minutes for a total of 5 hours, to determine the COOH concentration by titration. The investigation of reaction kinetic showed that reaction model Â could describe the kinetic of polyesterification shellac hydrolizate-phthalic anhydride, especially for temperature below 150 0C. The reaction rate constants were obtained as follows:k1 = 19.7 e (-3802.82/T) g/mgek.menitk2 = 29.4 e (-4062.30/T) g/mgek.menit